2020
DOI: 10.1097/md.0000000000021242
|View full text |Cite
|
Sign up to set email alerts
|

The effect of scalp electroacupuncture combined with Memantine in patients with vascular dementia

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 62 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…Acupuncture treatment can significantly increase the activity of SOD in the brain and reduce brain tissue damage caused by free radicals, indicating that the results in memory consolidation are closely correlated with changes in LPO and SOD in the brain [12]. In addition to this, the development of intelligence with acupuncture can be influenced through a routine and continuous stimulation process [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acupuncture treatment can significantly increase the activity of SOD in the brain and reduce brain tissue damage caused by free radicals, indicating that the results in memory consolidation are closely correlated with changes in LPO and SOD in the brain [12]. In addition to this, the development of intelligence with acupuncture can be influenced through a routine and continuous stimulation process [10].…”
Section: Discussionmentioning
confidence: 99%
“…This is because the Zhu Scalp acupuncture method works on the principle of reducing the level of lipid peroxidation in the brain, increasing the body's ability to scavenge reactive oxygen species, and oxidizing and preventing further damage, thereby contributing to patient recovery [18]. In Zhu Scalp the eding zone area is able to increase enthusiasm, eliminate fear, increase concentration and help the flow of qi and blood to the brain to be smooth so that the brain has sufficient nutrition to carry out its functions [12].…”
Section: Discussionmentioning
confidence: 99%
“…Dementia refers to a group of brain disorders that affect memory, reasoning, judgment, executive function, practice, visuospatial ability, and language that is not part of delirium or other major mental disorders. Vascular dementia accounts for 15%–20% of all cases of dementia patients and is the second most common type of dementia, just below AD 45 . The development of vascular cognitive impairment and vascular dementia is associated with the presence of damaging factors such as blockage and narrowing of blood vessels 46 .…”
Section: Memantine's Therapeutic Potential For Other Diseasesmentioning
confidence: 99%
“…Therefore, patients with cerebrovascular and cardiovascular disease are more likely to develop vascular dementia than normal individuals 47 . Unlike AD, no drug is clearly effective for vascular dementia, for which there is currently no approved treatment 45,48 . There is an urgent need to explore the pathogenesis and treatment methods of vascular dementia.…”
Section: Memantine's Therapeutic Potential For Other Diseasesmentioning
confidence: 99%
“…It is simple, convenient, economical and effective, and has been widely used in clinical practice in China [11]. Studies have demonstrated that electroacupuncture can improve cognitive impairment and learning and memory ability in patients with VaD by reducing inflammatory response [12,13] but the exact mechanism by which electroacupuncture reduces inflammatory response remains unclear. In this study, we use electroacupuncture intervened therapy VaD rats, aiming to explore whether electroacupuncture inhibits inflammation and improves cognitive function damage in rats is mediated by the Sirt1/STAT3 signaling pathway.…”
Section: Introductionmentioning
confidence: 99%